2011
DOI: 10.1177/1071181311551274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Text Format on Determining Tires' Date of Manufacture

Abstract: Previous research indicates that most consumers are unaware that older tires can deteriorate and lead to tread separation which could result in crashes. Even if they were to know about this hazard, the task of determining the date of manufacture (DOM) on tires is difficult. In the U.S., consumers must decode a 4 digit number at the end of a longer U.S. Department of Transportation (DOT) identification number in small, black print embossed onto black sidewalls. Eighty-three participants (45 students and 38 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Thus, tyres are very important components of vehicle composition and their safety must be assured and not neglected. This is because tyres are the only part of a vehicle that have direct contact with the roadway and expected to be robust enough to bear both the weight of the vehicle and its cargo through many thousands of miles of travel, while staying pliant enough to ensure passenger comfort [2]. Tyres are also expected to be durable and versatile enough.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, tyres are very important components of vehicle composition and their safety must be assured and not neglected. This is because tyres are the only part of a vehicle that have direct contact with the roadway and expected to be robust enough to bear both the weight of the vehicle and its cargo through many thousands of miles of travel, while staying pliant enough to ensure passenger comfort [2]. Tyres are also expected to be durable and versatile enough.…”
Section: Introductionmentioning
confidence: 99%
“…Tyre maintenance is one of the basic motor vehicle maintenance practices that is identified that drivers do not practice as recommended. For instance, according to [2], many drivers do not inflate tyres at the recommended pressure. This can result in tyre failure and loss of vehicle control and other side effects such as poor fuel economy [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations